Analisis Strategi Pengembangan Usaha Berbasis Business Model Canvas dan Analisis SWOT (Studi Kasus Café Kopgun Bandasari Kabupaten Bandung) - Rizza Regitha Astiana; Hendar Rubedo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Café Kopgun Bandasari is a micro, small, and medium enterprise (MSME) in the food and beverage sector located in Bandung Regency. Despite its advantages in distinctive coffee flavor sourced from its own plantation and an attractive natural atmosphere, the café still faces operational challenges, including long serving times, inconsistent product taste, customer queue build-ups, and inconsistent implementation of Standard Operating Procedures (SOP). This study aims to analyze the business model condition of Café Kopgun Bandasari using the Business Model Canvas (BMC) framework and to formulate a proposed improvement of SOP as a business development strategy based on SWOT analysis. This research employs a qualitative descriptive method, with data collected through in-depth interviews, observation, and documentation. Data were analyzed using the Miles and Huberman interactive model and further formulated into the SWOT Matrix, IFAS, and EFAS. The results show that Café Kopgun Bandasari has a strong Value Propositions element, namely its distinctive coffee flavor and authentic natural atmosphere, but shows significant weaknesses in the Key Activities and Key Resources elements due to habitual-based operations. The IFAS-EFAS analysis places the café at coordinates (0.25; 0.04), positioning it in Quadrant I (Strength–Opportunity), which indicates a growth-oriented strategy. The recommended priority strategies include formulating a Service SOP, a Production SOP, and a Promotion SOP to transform operational weaknesses into systemic strengths.